A Model for Mapping Interactivity in Learning Experiences - Tay, Jo Li Marie-Joelle (Curtin University, 2018)
This research is situated at the intersection of technology, education, and design. A design methodology was applied to examine the issues relating to interactivity within these disciplines. The result of this research is a working definition of interactivity aesthetics that can be used across multiple disciplines, and a model of interactivity as a practical means of evaluating the interactivity in any given learning experience.